Narrowing of the martensite transformation temperature hysteresis in ferromagnetic Fe-Co-Ni-Ti alloys doped with Cu - Kokorin, V.V.; Kozlova, L.E.; Perekos, A.E.; Levchuk, Yu.S.; Ruzhitskaya, T.V. (Functional Materials, 2008)
Using optical metallography and magnetic measurements, the structure and magnetic characteristics of the martensitic transformation have been studied in the Fe—Co—Ni—Ti alloys with copper additive. The copper doping has been found to reduce the temperature hysteresis width of the martensitic transformation down to ΔT ≈ 60°, the Curie point being maintained at a level near 300°C. It has been shown that the Fe—Ni—Co—Ti—Cu alloys may be of good prospects as materials where the mechanical characteristics could be controlled by magnetic field influence.